Answer:
The solution is x = 26
Step-by-step explanation:
Here, the given equation is,
![\frac{1}{3}(x-2)=\frac{1}{5}(x+4)+2](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D%28x-2%29%3D%5Cfrac%7B1%7D%7B5%7D%28x%2B4%29%2B2)
Add fractions on right side,
![\frac{1}{3}(x-2)=\frac{x+4+10}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D%28x-2%29%3D%5Cfrac%7Bx%2B4%2B10%7D%7B5%7D)
By cross multiplication,
![5(x-2)=3(x+14)](https://tex.z-dn.net/?f=5%28x-2%29%3D3%28x%2B14%29)
By distributive property,
![5x-10=3x+42](https://tex.z-dn.net/?f=5x-10%3D3x%2B42)
Adding 10 on both sides,
![5x=3x+52](https://tex.z-dn.net/?f=5x%3D3x%2B52)
Subtract 3x on both sides,
![2x=52](https://tex.z-dn.net/?f=2x%3D52)
Divide both sides by 2,
![x=26](https://tex.z-dn.net/?f=x%3D26)
Which is the required solution,
Last option is correct.